Modelling of Clay Ceramic Paste Composition in Production of Ceramic Tiles (Journal of University of Babylon for Engineering Sciences, 2022)
Ceramic materials are the most popular materials for different types of buildings. However, many obstacles meet the process of ceramic industry.Therefore, the aim of this paper is finding a new methodology to achieve the best mixture of ceramic paste depending on geotechnical properties of clay (Atterberg limit & grain size), thus by trying different mixtures and then comparing the specifications of a final product. Many mass formulations were tested in the laboratory at the optimal processing conditions (applied pressure and firing temperature). Then specific software is designed through modeling the experimental results for normalizing. The new software program is clay-ceramic pastes (CCP). CCP evaluates the raw material and checks the appropriate one for the desired final product.This research will contribute to minimize the random choices of raw materials and saving time through reducing the number of trials that were spent to reach to optimum formulation of ceramic paste.